Sobre Renate Pieper y Peer Schmidt (eds.), Latin America and the Atlantic World/ Essays in honor of Horst Pietschmann. El mundo atlántico y América Latina (1500-1850) - Hausberger, Bernd (Historia Mexicana, 2007)
-